2007
DOI: 10.1200/jop.0712504
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Practice Operations: Results From a Survey of Office-Based Oncology Practices

Abstract: The Medicare Modernization Act of 2003 1 brought with it sweeping changes to community-based oncology practices. As Medicare payment for both drugs and drug administration services have changed, oncology practices have become more aware of their business practices and have responded by closely evaluating and monitoring operations. In a January 2006 report to the Centers for Medicare & Medicaid Services and Congress, titled "The Effects of Medicare Payment Changes on Oncology Services," 2 the Medicare Payment A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…2 The survey was designed to be simple to complete, and virtually all questions from the 2006 survey were repeated in 2007.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The survey was designed to be simple to complete, and virtually all questions from the 2006 survey were repeated in 2007.…”
Section: Methodsmentioning
confidence: 99%
“…1 In 2006, Onmark, an Oncology Therapeutics Network (OTN) company, conducted the Office-Based Oncology Business Benchmarking Survey, and reported highlights of the results in the Journal of Oncology Practice. 2 Recognizing that community-based oncology has a strong desire to monitor and trend the key practice indicators (KPIs) that were established last year, the company conducted the second annual Business Benchmarking Survey in Spring 2007. The oncology-specific business benchmarks contained in this article update these KPIs and also compare the 2007 survey results with those from 2006.…”
mentioning
confidence: 99%
“…A 2006 national survey showed that drug expenses average 61% of an oncology practice's expenses in any given year, while in most other medical practices, drugs and supplies are a very small part of overall expenses. 1,2 Thus, in oncology practice, good management of drug purchasing and rigorous inventory control is essential for sound financial management. Although the oncologists typically do not get involved in managing the drug inventory, an important role for them is to be sure that a good system is in place.…”
Section: Pharmaceuticals: Controlling Inventory and Costsmentioning
confidence: 99%
“…The Assembly of Oncology and Hematology Administrators, an MGMA specialty assembly, developed additional survey questions to report benchmarks specifically for oncologyhematology and published an oncology-specific survey report for 2000, 1 2002, 2 and 2003. 3 Subsequent oncology survey data has been published in this journal for 2005 4 and 2006. 5 This article brings forward several benchmarks from all of these prior works and describes the results of a 2007 survey conducted by Oncology Metrics, llc.…”
Section: Introductionmentioning
confidence: 99%